A Evolution and Impact of Web Search Engines: A Comprehensive Review - Kunal Hiwale; Pratik More; Yogesh Nayake (Engineering And Technology Journal, 2024)
Web search engines have become indispensable tools in our daily lives, revolutionizing the way we access and navigate the vast expanse of information available on the internet. This research paper provides an in-depth analysis of the evolution, functioning, and impact of web search engines. Beginning with a historical overview, it traces the development of search engines from their inception to the present day. The paper explores the underlying technologies that power search engines, including crawling, indexing, and ranking algorithms. Furthermore, it examines the socio-economic implications of search engines, discussing their influence on information retrieval, online advertising, user behavior, and societal dynamics. Finally, the paper discusses current trends and future prospects in the field of web search engines.